Impact of Oral Hygiene on Prognosis in Patients With Squamous Cell Carcinoma of the Lower Gingiva - Zhao, Hui; Zhang, Shengnan; Ma, Jinji; Sun, Xiaodong (Frontiers in Surgery, 2021)
Objective: We aimed to analyze the significance of oral hygiene in patients with squamous cell carcinoma of the lower gingiva. Methods: Oral hygiene was assessed using a questionnaire by calculating the oral health (OH) score and the dental care (DC) score. The association of oral hygiene with clinical pathologic variables, disease free survival (DFS), and overall survival (OS) was analyzed. Results: Four out of 53 non-smokers and 19 out of 90 current or former smokers had an OH score of 6 (statistically significant difference, p=0.036). Fifteen out of 63 patients with a T3/T4 tumor and 8 out of 80 patients with a T1/T2 tumor had an OH score of 6 (statistically significant difference, p=0.026). Similar statistically significant findings were noted with respect to the DC scores, smoking status, and tumor stage. Among patients with an OH score of 0–5, the 5-year DFS and OS rates were 55% and 50%, respectively and among patients with an OH score >5, they were 46% and 43%, respectively (both differences statistically significant, p<0.05). Among patients with a DC score of 0–2, the 5-year DFS and OS rates were 69% and 51%, respectively and among patients with a DC score >2, they were 50% and 47%, respectively (both differences statistically significant, p<0.05). Cox model confirmed OH and DC scores as independent factors affecting the DFS and OS. Conclusion: Poor oral hygiene was associated with decreased DFS and OS.